PENGARUH LITERASI KEUANGAN, TANGGUNGAN KELUARGA, DAN KOMITMEN KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PRIBADI DI KALANGAN MAHASISWA PENERIMA BEASISWA KIP - Sudarma, Rizaldi Alfian; Tata, jan Felarius; Suruan, Ted; Orisu, Lillyani Margaretha (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2025)
This study aims to analyze the influence of financial literacy, family dependents, and commitment on personal financial management among KIP- scholarship recipients,. Personal financial management is a crucial skill for students, particularly those who rely on financial aid. This research applies a quantitative approach using a survey method, involving 235 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression to examine both partial and simultaneous effects of the independent variables on the dependent variable. The results show that financial literacy and commitment have a significant partial effect on personal financial management, while family dependents do not have a significant effect. However, simultaneously, all three variables have a significant impact. These findings highlight the importance of strengthening financial literacy and individual commitment to support students' ability to manage their scholarship funds wisely and responsibly. This study provides valuable insights for universities and scholarship providers in designing effective financial education and development programs for students.